Proteasome and Neuroprotective Effect of Hyperbaric Oxygen Preconditioning in Experimental Global Cerebral Ischemia in Rats - Ostrowski, Robert P.; Pucko, Emanuela; Matyja, Ewa (Frontiers in Neurology, 2022)
Objectives We investigated the involvement of the proteasome in the mechanism of preconditioning with hyperbaric oxygen (HBO-PC). Methods The experiments were performed on male Wistar rats subjected to a transient global cerebral ischemia of 5 min duration (2-vessel occlusion model) and preconditioned or not with HBO for 5 preceding days (1 h HBO at 2.5 atmosphere absolute [ATA] daily). In subgroups of preconditioned rats, the proteasome inhibitor MG132 was administered 30 min prior to each preconditioning session. Twenty-four hours and 7 days post-ischemia, after neurobehavioral assessment, the brains were collected and evaluated for morphological changes and quantitative immunohistochemistry of cell markers and apoptosis-related proteins. Results We observed reduced damage of CA1 pyramidal cells in the HBO preconditioned group only at 7 days post-ischemia. However, both at early (24 h) and later (7 days) time points, HBO-PC enhanced the tissue expression of 20S core particle of the proteasome and of the nestin, diminished astroglial reactivity, and reduced p53, rabbit anti-p53 upregulated modulator of apoptosis (PUMA), and rabbit anti-B cell lymphoma-2 interacting mediator of cell death (Bim) expressions in the hippocampus and cerebral cortex. HBO-PC also improved T-maze performance at 7 days. Proteasome inhibitor abolished the beneficial effects of HBO-PC on post-ischemic neuronal injury and functional impairment and reduced the ischemic alterations in the expression of investigated proteins. Significance Preconditioning with hyperbaric oxygen-induced brain protection against severe ischemic brain insult appears to involve the proteasome, which can be linked to a depletion of apoptotic proteins and improved regenerative potential.